Ada Twist's Big Project Book for Stellar Scientists - Beaty, Andrea; Roberts, David, 1970- (New York : Abrams Books for Young Readers, 2018)
"For curious young minds who ask why? how? what? when? and then why? again and again, the bestselling team behind Ada Twist, Scientist has developed a STEM project book based on the beloved character. Ada herself will take readers through the scientific method and introduce them to some of her favorite sciences, including chemistry, botany, astronomy, and environmental science. Budding scientists will solve everyday mysteries and come to think more critically about the world around them. Like Rosie's and Iggy's project books, Ada's will be empowering and kid-friendly, with tons of classroom and parent appeal. No kid's lab would be complete without it!"--
Keywords: Science -- Experiments -- Juvenile literature; Science -- Study and teaching -- Juvenile literature; Science -- Experiments; Science -- Study and teaching; Juvenile works; Nonfiction